Pentingnya Pemahaman Multikulturalisme dalam Resolusi Konflik Pembangunan GKI Yasmin Bogor Guna Mewujudkan Keamanan Nasional - Arifuddin Uksan (Mahesa Research Center, 2023)
This paper aims to analyze the importance of understanding multiculturalism in knitting diversity into a force of peace in resolving conflicts over the construction of the GKI Yasmin house of worship, Bogor. The problem is focused on understanding multiculturalism on the formation of people's mindsets, attitudes and behavior. In order to approach this problem, theoretical references from Tilaar, Lawrence Blum, Baedhawy and Galtung are used. The data collected in this study are data obtained from field research through interviews, observation and documentation at the source of the conflict which were analyzed using qualitative methods. This study concludes that the understanding of multiculturalism is very decisive in the resolution of conflicts over the construction of the GKI Yasmin house of worship in Bogor City. This conclusion is based on the low understanding of multiculturalism in the Bogor City community and evidenced by the occurrence of horizontal conflicts. If this condition is left without efforts to resolve it, it will become a prolonged SARA conflict. In addition, weaknesses were also found in preventing conflict in the aspect of the role of local government in implementing regulatory policies that were not quite right.